Clinical stabilization of a highly refractory acute myeloid leukaemia under individualized treatment with immune response modifying drugs by in vivo generation of dendritic cells of leukaemic origin (DCleu) and modulation of effector cells and immune escape mechanisms - Giuliano Filippini Velázquez; Philipp Anand; Joudi Abdulmajid; Xiaojia Feng; Jan Frederic Weller; Klaus Hirschbühl; Helga Schmetzer; Christoph Schmid (Biomarker Research)
Abstract The conversion of leukemic blasts into antigen-presenting dendritic cells of leukemic origin (DCleu) by GM-CSF and PGE1 has demonstrated preclinical efficacy in eliciting leukaemia-specific immune responses, offering a promising immunotherapeutic strategy for relapsed/refractory AML. We report on a 65-year-old patient with AML refractory to multiple treatment lines, including two allogeneic stem cell transplantations, who received individualized experimental treatment with intravenous GM-CSF and PGE1 and no additional anti-leukaemic therapy. Based on preceding ex-vivo treatment of patient´s blood with GM-CSF/PGE1 that showed immune activation and blast lysis, we hypothesized that intravenous administration of the compounds to the patient would promote in-vivo antileukaemic immune reactions and potentially induce clinical response. Eight treatment cycles were administered, and extensive immune monitoring was performed. The treatment was well tolerated and resulted in sustained clinical stabilization over four months. Immune monitoring showed generation of mature DCleu, activation of leukaemia-directed effector and memory cells (including IFN-γ–producing and degranulating T and NK cells), downregulation of immune checkpoint (PD-1/CTLA-4) expressing T cells and blasts, and a reduction in regulatory B- and T cells. This case illustrates the feasibility and tolerability of GM-CSF + PGE1 therapy and its potential to modulate anti-leukaemic immunity in a patient with highly refractory AML.